(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
During the 2nd and 1st centuries BCE the Palaeoeuropean written culture reached, on the one hand, its maximum intensity, diversification and geographic expansion, but, on the other, it underwent the pressure of the powerful Latin written culture that ended up imposing itself until causing the extinction of the written use of Palaeoeuropean languages. The role of Rome in this process was decisive in creating a common framework of relations in western Europe, promoting written culture and helping to spread new stimuli, many of them of Hellenistic origin but reworked in Rome, among which the use of public inscriptions as a means of social communication. The reactions of local cultures varied greatly, but always with predominance of the vernacular languages and writings in the written manifestations.